Foresight IMPACT model training: feedback survey report - Schuetz, Tonya; Sulser, Timothy B.; Hartley, Faaiqa; Gabriel, Sherwin; Mishra, Abhijeet; Petsakos, Athanasios; Cali', Davide (2024)
To capture the changes towards outcomes from the provided IMPACT model training sessions, a survey was conducted after the training. The survey was sent to 35 recipients and there were 20 responses provided between 19 April to 3 May 2024, i.e. a response rate of 57%. Overall, the results revealed an increase in level of confidence and knowledge of around 30% across the questions related to the before (39-53%) and after the training (70-78%) section. This report presents some more details on the results and feedback received from participants to the questions (see Annex 1 for survey questions). We use these as guidance as to how to improve in the future as well as inform possible future activities and follow-up questions.